Whose Issue Is It Anyway? The Effects of Leader Gender and Equality Message Framing on Men’s and Women’s Mobilization Toward Workplace Gender Equality - Hardacre, Stephanie L.; Subašić, Emina (Frontiers in Psychology, 2018)
Social psychologists have not fully investigated the role of leadership in mobilising widespread support for social change, particularly gender equality. The burden of achieving gender equality is typically placed on women (particularly female leaders) - the main targets of such inequality. Traditional approaches frame workplace gender equality as either a women’s issue, which limits men’s (non-target’s) involvement in the movement, or a meritocratic non-issue that exists due to women’s (target’s) tendency to pursue less intensive careers. In contrast to such work focusing on women’s experiences as targets of discrimination or men’s role in preserving inequality, we propose a solidarity-based approach that positions men and women as agents of change. This approach relies on two processes: leadership processes – particularly leadership as a form of influence based on shared identities among leaders and followers (e.g., their gender group); and political solidarity as a way to mobilise the silent majority (men) to work as allies beside a minority (women) and embrace equality as a common cause for both groups. In two experiments (Ns=338, 336) we studied how leader gender and message framing affect men’s and women’s support for equality by contrasting a solidarity-based framing of gender equality as a common cause for men and women, with a women’s issue frame (Experiment 1) or a meritocratic frame (Experiment 2). The statement was attributed to a male or female leader (Experiments 1-2) or, additionally, to a government agency (Experiment 1). Women reported higher sense of common cause (Experiment 2) and collective action intentions than men (Experiments 1-2), and higher intentions under common cause compared to meritocracy frames (Experiment 2). Interestingly, male leaders invoked higher sense of common cause and collective action intentions for both men and women regardless of framing (Experiment 2). Irrespective of leader gender however, as predicted common cause framing boosted perceived leader prototypicality, legitimacy, and influence across the board (Experiments 1-2). Yet this was qualified by women (compared to men) rating leaders as more legitimate and influential under common cause compared to meritocracy framing (Experiment 2).Women’s reactions to equality messages, and the intersection of leadership and solidarity towards equality are discussed.